(untitled) (Journal of Science and Technology, 2016)
The operations of a commercial hatchery in Ghana were studied and records covering a period of thirteen months were compiled and analyzed. The hatchery studied is a unit of a fully integrated form. Its eggs were stored in an air-conditioned room and were set twice in a week. The layer chicks were harvested on Mondays and broiler chicks on Thursdays. The records indicated that 775,403 broiler eggs were set and 595,709 saleable broiler chicks were hatched. This represented 76.8% of eggs set and 85.1% of fertile eggs. Out of the 835,539 layer eggs set, a total of 623,841 saleable chicks (50% 1% pullet chicks and 49.9% cockerel chicks) were hatched, the saleable chicks value was 74.7% of eggs set and 89.9% of fertile eggs in both broilers and layers fertility declined with advancing age of the breeders. The problems observed and their possible solutions have been discussed. The operations of a commercial hatchery in Ghana were studied and records covering a period of thirteen months were compiled and analyzed. The hatchery studied is a unit of a fully integrated form. Its eggs were stored in an air-conditioned room and were set twice in a week. The layer chicks were harvested on Mondays and broiler chicks on Thursdays. The records indicated that 775,403 broiler eggs were set and 595,709 saleable broiler chicks were hatched. This represented 76.8% of eggs set and 85.1% of fertile eggs. Out of the 835,539 layer eggs set, a total of 623,841 saleable chicks (50% 1% pullet chicks and 49.9% cockerel chicks) were hatched, the saleable chicks value was 74.7% of eggs set and 89.9% of fertile eggs in both broilers and layers fertility declined with advancing age of the breeders. The problems observed and their possible solutions have been discussed.